2002
DOI: 10.1136/sti.78.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections in Bangladeshis resident in the UK: a case-control study

Abstract: Objective: To evaluate the prevalence of sexually transmitted infections (STIs) and mode of presentation in patients originating from Bangladesh and resident in the United Kingdom in comparison with non-Bangladeshi patients attending an inner London genitourinary medicine (GUM) clinic. Methods: A retrospective, cross sectional study with comparator group was carried out at an open access GUM clinic in east London. 104 consecutive newly attending Bangladeshi men were compared with 199 consecutive newly attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…This may indicate poorer access to GU medicine services, possibly a reflection of cultural and socioeconomic barriers to health-care access. These results confirm findings by Skinner et al 5 who found that Bangladeshi GU medicine clinic attendees were also more likely to be referred to GU medicine services than selfreferred. This is a large, well-designed study; however, there are limitations.…”
Section: Discussionsupporting
confidence: 95%
“…This may indicate poorer access to GU medicine services, possibly a reflection of cultural and socioeconomic barriers to health-care access. These results confirm findings by Skinner et al 5 who found that Bangladeshi GU medicine clinic attendees were also more likely to be referred to GU medicine services than selfreferred. This is a large, well-designed study; however, there are limitations.…”
Section: Discussionsupporting
confidence: 95%
“…Our results are consistent with other studies that have reported how GUM clinics are seldom the first port of call for South Asians seeking STI care, and that South Asian GUM attendees are less likely than other attendees to self-refer, instead being more likely to be referred from other medical services such as general practice or family planning 12 13. While higher referral rates may reflect higher attendance rates by South Asians at non-GUM services, others suggest that this healthcare-seeking behaviour reflects a low perception of sexual health risk among South Asians,14 their lack of awareness of GUM services15 16 and their association of GUM services with stigma, such that the anxiety of being recognised attending a clinic acts as a barrier to access 15.…”
Section: Discussionsupporting
confidence: 92%
“…Use of condoms and IUDs was higher among Asian women than white women. Ross et al 52 Saxena et al 21 Saxena et al 39 Sethi et al 33 Sinha et al 13 Skinner et al 27 …”
Section: Resultsmentioning
confidence: 99%
“…25,26 One GUM clinic study found similar rates of STIs in Bangladeshi attendees as non-Bangladeshi attendees, though this was mainly among individuals born in Bangladesh. 27 Bangladeshi men were also more likely than non-Bangladeshis to present with sexual dysfunction, and both men and women were more likely to have been referred to GUM from general practice and family planning services. Sexual dysfunction and premature ejaculation among some South Asian and Muslim men has been found elsewhere.…”
Section: Stis and Hivmentioning
confidence: 99%